2022
DOI: 10.1051/0004-6361/202142583
|View full text |Cite
|
Sign up to set email alerts
|

Emission from HCN and CH3OH in comets

Abstract: Aims. The aim of this work is to characterise HCN and CH3OH emission from recent comets. Methods. We used the Onsala 20-m telescope to search for millimetre transitions of HCN towards a sample of 11 recent and mostly bright comets in the period from December 2016 to November 2019. Also, CH3OH was searched for in two comets. The HCN sample includes the interstellar comet 2I/Borisov. For the short-period comet 46P/Wirtanen, we were able to monitor the variation of HCN emission over a time-span of about one month… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
4
3
1
Order By: Relevance
“…Our CN/OH ratios are in agreement with the HCN/H 2 O ratios derived directly from IR observations around the same dates, namely, Dec. 16-23, 2018 (see Table 2). In addition, the HCN production rates (1.06±0.03)×10 25 molec/s obtained from millimeter (Biver et al 2021) and (1.60±0.10)×10 25 molec/s from sub-millimeter observations (Bergman et al 2022) show an agreement with our Q(CN) values obtained during the same nights of Dec. 15 and 20. This indicates that the observed CN abundances are consistent with HCN being the dominant parent.…”
Section: Parent and Daughter Moleculessupporting
confidence: 89%
See 1 more Smart Citation
“…Our CN/OH ratios are in agreement with the HCN/H 2 O ratios derived directly from IR observations around the same dates, namely, Dec. 16-23, 2018 (see Table 2). In addition, the HCN production rates (1.06±0.03)×10 25 molec/s obtained from millimeter (Biver et al 2021) and (1.60±0.10)×10 25 molec/s from sub-millimeter observations (Bergman et al 2022) show an agreement with our Q(CN) values obtained during the same nights of Dec. 15 and 20. This indicates that the observed CN abundances are consistent with HCN being the dominant parent.…”
Section: Parent and Daughter Moleculessupporting
confidence: 89%
“…Moulane-corr (McKay et al 2021;Khan et al 2021;Roth et al 2021a), search for icy grains in the coma (Protopapa et al 2021;Bonev et al 2021), and coma features from optical imaging (Knight et al 2021). Millimeter and submillimeter observations of 46P have reported on the detection of several complex organic molecules and showed that the comet is relatively rich in methanol, but relatively depleted in CO, CS, HNC, HNCO, and HCOOH (Biver et al 2021;Roth et al 2021b;Coulson et al 2020;Bergman et al 2022). Using both TRAPPIST-North (TN) and TRAPPIST-South (TS), we collected photometric observation over almost a year.…”
Section: Introductionmentioning
confidence: 99%
“…On 2018 December 21, we obtained a mixing ratio of ∼0.2% using comeasured Q(H 2 O). The HCN production rate of (1.57 ± 0.12) × 10 25 mol s −1 obtained by Bergman et al (2022) on 2018 December 20 was within the range of values that we obtained for 2018 December 21. Biver et al (2021) obtained an average HCN mixing ratio of (0.11 ± 0.01)% from millimeterwave observations of 46P spanning 2018 December ∼12-25.…”
Section: Hcnsupporting
confidence: 87%
“…Hydrogen cyanide (HCN) is a precursor in the synthesis of amino acids, and thus an important organic for understanding the emergence of life. Bergman et al (2022) used millimeterwave observations and radiative transfer modeling to obtain HCN mixing ratios of (0.10 ± 0.01)% and (0.19 ± 0.02)% in 46P on 2018 December 21, using H 2 O production rates from Combi et al (2020) and Bonev et al (2021), respectively. On 2018 December 21, we obtained a mixing ratio of ∼0.2% using comeasured Q(H 2 O).…”
Section: Hcnmentioning
confidence: 99%
“…It should be noted that similar results were recently observed by Bergman et al (2022) in the case of HCN. By running time-dependent radiative transfer calculations, these authors were able to quantify these effects and they have shown that the photodissociation and expansion processes do actually modify the HCN level populations by less than 15%.…”
Section: Data Availabilitysupporting
confidence: 89%